2010
DOI: 10.1007/s00125-010-1773-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of peroxisome proliferator-activated receptor gamma, coactivator 1 alpha (PGC-1α) improve lipid utilisation, insulin signalling and glucose transport in skeletal muscle of lean and insulin-resistant obese Zucker rats

Abstract: Aims/hypothesis Reductions in peroxisome proliferatoractivated receptor gamma, coactivator 1 alpha (PGC-1α) levels have been associated with the skeletal muscle insulin resistance. However, in vivo, the therapeutic potential of PGC-1α has met with failure, as supra-physiological overexpression of PGC-1α induced insulin resistance, due to fatty acid translocase (FAT)-mediated lipid accumulation. Based on physiological and metabolic considerations, we hypothesised that a modest increase in PGC-1α levels would li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 51 publications
(138 reference statements)
12
110
5
2
Order By: Relevance
“…Whereas the findings from these transgenic animals have been disappointing, it appears that more modest increases in the level of the PGC-1 coactivators (e.g. two-to threefold in the current study and [25,26]) avoid many of the unanticipated consequences of excessive transgene expression and result in beneficial effects with regards to insulin sensitivity. Numerous studies have demonstrated that insulin resistance is linked with increased amounts of various deleterious lipid intermediates within skeletal muscle [1,2].…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Whereas the findings from these transgenic animals have been disappointing, it appears that more modest increases in the level of the PGC-1 coactivators (e.g. two-to threefold in the current study and [25,26]) avoid many of the unanticipated consequences of excessive transgene expression and result in beneficial effects with regards to insulin sensitivity. Numerous studies have demonstrated that insulin resistance is linked with increased amounts of various deleterious lipid intermediates within skeletal muscle [1,2].…”
Section: Discussioncontrasting
confidence: 57%
“…An enhanced capacity for mitochondrial substrate oxidation in skeletal muscle has been linked with improved insulin action [8,9,25,26]. In the current study, rats fed an HFD displayed clear insulin resistance at the whole-body and muscle level.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Basal and insulin-stimulated 3-O-methylglucose uptake was measured using a submaximal concentration of insulin (150 μU/ml) in perfused rat hindlimb muscles as we have described previously [12,20].…”
Section: Basal and Insulin-stimulated Glucose Uptakementioning
confidence: 99%
“…Moreover, three genes including SOCS3 (suppressor of cytokine signaling 3), PPARGC1A (peroxisome proliferator-activated receptor gamma, coactivator 1 alpha) and ACC2 (acetyl-CoA carboxylase beta) were included in the EXP1 dataset. Both PPARGC1A and ACC2 are involved in the regulation of fatty acid oxidation [54,55]. Though SOCS3 cannot directly influence fatty acid oxidation, it inhibits leptin activation of AMPK (5′ AMP-activated protein kinase) [56].…”
Section: Identifying Representative Genes In the Adipocytokine Signalmentioning
confidence: 99%